2020
DOI: 10.3390/nu12020375
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behavior (Duration, Content, and Timing) Among Workers Living under Different Levels of Urbanization

Abstract: Urbanization has contributed to extended wakefulness, which may in turn be associated with eating over a longer period. Here, we present a field study conducted in four groups with different work hours and places of living in order to investigate eating behavior (duration, content, and timing). Anthropometric measures were taken from the participants (rural (n = 22); town (n = 19); city-day workers (n = 11); city-night workers (n = 14)). In addition, a sociodemographic questionnaire was self-answered and 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This essentially creates the pre-conditions for increased UPF consumption inside and outside of home, and unhealthy eating and cooking habits (e.g., eating late at night), which may lead eventually to an increased risk of non-communicable diseases. This linkage between urban form, lifestyle, and diet change has been identified in some urban contexts of SSA and elsewhere (Tiuganji et al 2020 ; Bren d’Amour et al 2020 ; Khonje and Qaim 2019 ).…”
Section: Discussionmentioning
confidence: 66%
“…This essentially creates the pre-conditions for increased UPF consumption inside and outside of home, and unhealthy eating and cooking habits (e.g., eating late at night), which may lead eventually to an increased risk of non-communicable diseases. This linkage between urban form, lifestyle, and diet change has been identified in some urban contexts of SSA and elsewhere (Tiuganji et al 2020 ; Bren d’Amour et al 2020 ; Khonje and Qaim 2019 ).…”
Section: Discussionmentioning
confidence: 66%
“…A 12-month follow-up study post-lifestyle intervention reported those who slept less than 6 h/day had a smaller reduction in waist circumference compared to those who slept more than 7 h/day [56]. Sleep and chrono-nutrition is interrelated, as it was shown that short sleepers were associated with longer eating windows [57], which could lead to greater food intake [58]. Despite this, both chronotypes demonstrated a reduction in total eating window post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, shift workers are asked about sleep and wake times during very specific shift scenarios based on the MCTQ Shift [28]; hence, it can only determine the temporal patterns of eating but not chronotype or sleep pattern of shift workers with certain patterns of rotating shift work or who perform split shifts. Secondly, we chose to capture the spread of energy distribution across the day based on the time of largest meal amidst times of main meals and snacks, instead of by calorie intake at set time intervals (e.g., 0900-1200 h, 1200-1500 h) across the day as in previous studies [75,76]. This approach chosen will be investigated in a subsequent study by comparison against food diaries completed within the same time frame.…”
Section: Discussionmentioning
confidence: 99%